Maternal High-Fat Diet During Pre-Conception and Gestation Predisposes Adult Female Offspring to Metabolic Dysfunction in Mice - Akhaphong, Brian; Gregg, Brigid; Kumusoglu, Doga; Jo, Seokwon; Singer, Kanakadurga; Scheys, Joshua; DelProposto, Jennifer; Lumeng, Carey; Bernal-Mizrachi, Ernesto; Alejandro, Emilyn U. (Frontiers in Endocrinology, 2022)
The risk of obesity in adulthood is subject to programming in the womb. Maternal obesity contributes to programming of obesity and metabolic disease risk in the adult offspring. With the increasing prevalence of obesity in women of reproductive age there is a need to understand the ramifications of maternal high-fat diet (HFD) during pregnancy on offspring’s metabolic heath trajectory. In the present study, we determined the long-term metabolic outcomes on adult male and female offspring of dams fed with HFD during pregnancy. C57BL/6J dams were fed either Ctrl or 60% Kcal HFD for 4 weeks before and throughout pregnancy, and we tested glucose homeostasis in the adult offspring. Both Ctrl and HFD-dams displayed increased weight during pregnancy, but HFD-dams gained more weight than Ctrl-dams. Litter size and offspring birthweight were not different between HFD-dams or Ctrl-dams. A significant reduction in random blood glucose was evident in newborns from HFD-dams compared to Ctrl-dams. Islet morphology and alpha-cell fraction were normal but a reduction in beta-cell fraction was observed in newborns from HFD-dams compared to Ctrl-dams. During adulthood, male offspring of HFD-dams displayed comparable glucose tolerance under normal chow and HFD re-challenge for 32 weeks. Adult female offspring of HFD-dams demonstrated normal glucose tolerance but displayed increased insulin resistance relative to controls under normal chow diet. Moreover, adult female offspring of HFD-dams displayed increased insulin secretion in response to high-glucose treatment, but beta-cell mass were comparable between groups. Together, these data show that maternal HFD at pre-conception and during gestation predisposes the female offspring to insulin resistance in adulthood.